Strategic innovations and interdisciplinary perspectives in telecommunications and networking - Meghanathan, Natarajan 1977- (IGI Global, 2019)
"This book examines timely and important telecommunications and networking issues, problems, and solutions from a multidimensional, interdisciplinary perspective for researchers and practitioners. It emphasizes the cross-disciplinary viewpoints of electrical engineering, computer science, information technology, operations research, business administration, economics, sociology, and law"--